Exploring the evolution of facial feminization and masculinization surgery: a bibliometric analysis and visualization study - Omer Uranbey; Omer Faruk Kaygisiz; Ferhat Ayrancı; Saim Yanik (SpringerOpen, 2024)
Abstract Background This study aims to conduct a bibliometric analysis of the current literature related to facial feminization surgery (FFS) and facial masculinization surgery (FMS) to understand the patterns, trends, and evolution of research topics. In addition, it aims to objectively identify the important articles that constitute the primary backbone of the FFS/FMS literature and provide a resource for education and new studies in this emerging field. Results Using the principles of the Leiden Manifesto, 384 publications from the Web of Science from 1987 to 2023 were analyzed. The analysis included cross-country collaboration, keyword trends, affiliations, co-citation networks, and clustering. The results showed an increasing trend in FFS/FMS publications, with the USA leading in both publications (n = 238) and citations (n = 2420). The most cited journal was the Journal of Plastic and Reconstructive Surgery. The results indicate a high growth rate, with an H-index of 34 and an average citation of 11.41 per article. Co-occurrence analysis revealed evolving keywords such as "forehead" (n = 52) and "quality of life" (n = 44). The timeline view illustrated the terms reflecting current areas of interest such as #patient satisfaction and #gender-affirming care. Conclusion The study reveals the influence of countries, institutions, authors, and emerging trends, supporting the anticipation that FFS/FMS will be a critical field of study in the future. The findings contribute to understanding the global landscape of FFS/FMS research, facilitating informed decision-making for researchers, and clinicians in the field of maxillofacial surgery.